Intensive versus guideline blood pressure and lipid lowering in patients with previous stroke: main results from the pilot ‘Prevention of decline in cognition after stroke trial’ (PODCAST) randomised controlled trial - Bath, Philip M.W.; Scutt, Polly; Blackburn, Daniel J.; Ankolekar, Sandeep; Krishnan, Kailash; Ballard, Clive; Burns, Alistair; Mant, Jonathan; Passmore, Peter; Pocock, Stuart; Reckless, John; Sprigg, Nikola; et al. (Public Library of Science, 2017)
Background